2014
DOI: 10.3329/bmj.v40i3.18651
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life Among Adult Migrant Garment Workers in Dhaka City

Abstract: The objective of this cross-sectional study was to assess the health-related quality of life among adult migrant garment workers (age 18-59 years) in Dhaka city. The study was conducted with 400 workers for quantitative research, and two health care service providers for qualitative research. Data were collected during February to March 2009. Data were collected by face-to-face interviews using a constructed pre-tested questionnaire adapted from WHOQOL-BREF. Data were analyzed by applying descriptive statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Living with family and relatives (AOR=3.63; 95%CI: 2.42-5.45; p<0.001) means that migrant workers have greater levels of responsibility in their daily life. In a Bangladeshi study, living with at least one family member was highly associated with low QOL (p=0.01) 13 . In the context of Cambodia, migrant workers often live in a small cottage where they work together with many family members, relatives or friends.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Living with family and relatives (AOR=3.63; 95%CI: 2.42-5.45; p<0.001) means that migrant workers have greater levels of responsibility in their daily life. In a Bangladeshi study, living with at least one family member was highly associated with low QOL (p=0.01) 13 . In the context of Cambodia, migrant workers often live in a small cottage where they work together with many family members, relatives or friends.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…A study in Dhaka city, Bangladesh showed that 94% of adult migrant workers in garment manufacture had low QOL, with only 3.25% and 2.75% having moderate and high QOL respectively. This may be due to the study in Bangladesh recruiting more female than male workers; within Indianite cultures, the female gender is devalued and females are perceived as the inferior gender, both physically and psychologically, resulting in very low QOL compared to males 13 . The above results demonstrate the inconsistency of QOL findings across the literature.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Across occupations, workers have different levels of HRQoL. [2][3][4][5] A study in China found that the HRQoL of farmers was higher than industrial workers. 3 According to Islam et al, 4 94% of migrant workers in Dhaka city reported a low level of HRQoL.…”
Section: Introductionmentioning
confidence: 99%